THE EFFECT OF PHYSICAL WORK ENVIRONMENT TO EMPLOYEES’ PERFORMANCE DURING WORK FROM HOME PROGRAM - Muhardi, Aristianto; Perdhana, Mirwan Surya (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT. As a result of the deadly Corona virus pandemic at the end of 2019, many companies have had to comply with government decisions regarding the implementation of the Work from Home (WFH) program for businesses around the world to suppress the spread of COVID-19. This decision has an impact on companies and employees in the city of Semarang who must make the transition to working from home by teleworking. With the high index of technological development in Indonesia showing a drastic increase from the previous year regarding the use of internet and technology create a supportive conditions for the implementation of the work from home program for employees in the city of Semarang, The theory of stimulus-response is used in this study to investigate the influence of employee’s physical work environment conditions during the transition to changes in the work from home program to employees performance. Data obtained from 150 respondents in Semarang City were analyzed using a structural equation model (SEM) using the partial least squares (PLS) method in the SmartPLS application. Open questions were also used in this research as additional information to show the background conditions of the work environment experienced by respondents during the work-from-home program. The results from the report's findings show that workspace design or layout, ambiance conditions, and work equipment all have a positive and significant impact on employee performance. Consequently, in this research, all hypotheses were accepted. The management implications of this study are intended to provide suggestions for increasing employees work performance during the work from home program by making regulatory schemes and recommendations regarding things that employees must do regarding the workspace design or layout, implementing disciplinary reports, and considering the background of prospective employees with the space availability and workspace comfort that employees have at home during the recruiting program.